PERBANDINGAN MODEL KEPEMIMPINAN DAN MANAJEMEN DALAM BINGKAI FILSAFAT PENDIDIKAN: SUATU KAJIAN KRITIS TERHADAP REALITAS, NILAI, DAN TUJUAN SEKOLAH - Sobari; Deden Yudi; Desita Purwati Sundari; Rina Farida Aryani; Irma Latifah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Leadership and management are two essential pillars in achieving effective educational practices. This study aims to critically examine various models of educational leadership and management through the lens of educational philosophy, focusing on empirical realities, underlying values, and the core objectives of schools. The research adopts a qualitative descriptive approach using literature review and content analysis techniques, exploring leadership models such as transformational, instructional, democratic, and visionary, as well as management models including school-based management, strategic management, total quality management (TQM), performance-based management, and humanistic approaches. The findings indicate that no single model is universally ideal across all school contexts. Transformational and instructional leadership are effective in enhancing the quality of teaching and learning, while school-based and strategic management offer autonomy and long-term planning advantages. Within the framework of educational philosophy, these models embody values of humanity, participation, and transformative orientation which, when applied contextually, can foster a healthy, collaborative, and learner-centered school environment. This study highlights the importance of educational leaders who are adaptive, reflective, and capable of integrating managerial and philosophical approaches in strategic decision-making. The findings reinforce the role of educational philosophy as a foundational guide for developing relevant and sustainable leadership and management patterns in schools.